EMBRACING CYBERSPACE: MALAYSIA AND THE CYBER SECURITY INITIATIVES - ZULHUDA, Sonny (Cyberpolitik Journal, 2023)
With the proliferation of digital technology and the adoption of digital innovation in the realm of social and political lives, governments worldwide must be ready to embrace the digital challenges. Malaysia, refusing to be left behind, aims to restart and rejuvenate its socioeconomic development for long-term sustainability and prosperity by restructuring the economy as the foundation in improving the wellbeing of the people. Central to the agenda of the economy is the strengthening of the country’s digital economy. With an accelerated digital technology adoption both at public and private sectors, extending the effect of digitalization to organizational and individual lives. Meanwhile, it is axiomatic that enhancing national security and unity is a game-changer for nation-building. The need for these national objectives cannot be over-emphasised in the context of digital economy, because the nation will ultimately face those challenges and we shall come prepared. It is important to remind that in the context of digital economy, cyber security stands out as a prerequisite for Malaysia to enjoy a secured, trusted and resilient cyberspace for everyone. A comprehensive national effort for enhancing our cyber security is crucial, so that we can make the best of the digital economy and eliminate all those risks that will threaten our digital sustainability. This paper stands to remind that for the nations and governments to sustain this digital realm, having a nationally-coordinated effort towards the security of its critical information infrastructure is a necessity instead of luxury.